Psychological capital and work engagement in relation to job performance among Pakistani teachers - Latif, Humaira (2017)
This thesis examines associations between positive psychological capital (PsyCap), work engagement, and performance among teachers in Pakistan. A sequential mixed methods design was applied that involved two studies. The first involved a cross-sectional survey of Pakistani teachers (N = 675) that sought to quantitatively establish the nature and strength of relations between PsyCap, work engagement, and job performance. The second was a qualitative study that involved six focus groups with the intention of discursively examining the mechanisms linking PsyCap, work engagement, and job performance. In both studies, teachers were divided into three strata: School, college, and university. A number of significant findings were identified. Overall, the findings from the quantitative study showed that PsyCap and work engagement were additively linked to job performance. PsyCap accounted for relatively large portions of variance in performance compared to work engagement. The results from the qualitative study confirmed and extended the findings of Study 1. Thematic analysis was used to analyse the focus group transcripts. Seven main themes were identified along with a further set of sub-themes. The key themes that emerged were teachers’ role in students’ lives, teachers’ understanding of their job performance. PsyCap and its mechanism, significance of work engagement, PsyCap and work engagement, and demographic and religious factors. The findings shed light on the mechanisms underpinning the positive relationship between PsyCap, work engagement, and performance among teachers, highlighting the role of religious factors within these relationships. The overall results of the current investigation highlight the nature and strength of relationships between PsyCap and performance, and work engagement and performance, and reinforce the value of utilising PsyCap and work engagement in organisational research to enhance performance. Future research should involve other occupational groups to explore the broader application of this framework.